Produção de biossurfactante por cândida sphaerica UCP 0995 para aplicação na remoção de poluentes ambientais gerados pela indústria de petróleo. - Santos, Emília Mendes da Silva (2019)
The biosurfactants are compounds of microbial origin and present numerous advantages over synthetic surfactants, such as structural diversity, low toxicity, biodegradability, ability to act in extreme environments, and to be produced from renewable sources. Therefore, the present study aims to maximize the production of a surfactant agent from Candida sphaerica UCP 0995 using industrial waste as low cost substrates in a 4 L bioreactor from a central point factorial design 23. The effects and interactions of the agitation speed (150, 175, 200, 250 and 275rpm), aeration (0, 0.5, 1.0, 1.5 and 2.0vm) and culture time (96, 108, 120, 132 and 144h) on surface tension and yield were evaluated. The results showed that the best obtained condition was, in medium containing shaking of 175 rpm, aeration of 1.5 vvm and culture time of 132 hours, with a reduction of the surface tension of 25.00 mN / m and a yield in biosurfactant of 8.50 g / L and a Critical Micellar Concentration of 0.2 g / L. The tensioactive and emulsifying capacity of the biosurfactant was investigated under extreme conditions of temperature, salinity and pH, indicating their stability. The investigation of the chemical composition by infrared spectroscopy, magnetic resonance and gas chromatography revealed that the biosurfactant studied is a glycolipid. MTT Cytotoxicity tests were performed by the MTT method against the cell line L929 (mouse fibroblast), where it was observed that it did not present cytotoxicity in the biosurfactant concentrations tested.the biosurfactant was subjected to different methodologies to be formulated as a commercial additive. The biomolecule was stable for 120 days at room temperature 28°C after addition of potassium sorbate as a preservative. Bioremediation tests were performed to analyze the efficacy of the isolated biosurfactant and its microbial producer producing oil in soil and contaminated sea water. The crude or isolated biosurfactant showed efficiency in the removal of 67% - 70% of the motor oil in contaminated soil under static conditions. Already for the kinetic tests removal of 90% of the motor oil contained in soil was removed in the period of 90 days. While the tests performed on sea water were obtained 85% oil removal. According to the results obtained, the biosurfactant of C. spaherica UCP 0995 presents promising properties as remediation agents of hydrophobic compounds in waters and soils.